Morphological diversity variation of seed traits among 587 germplasm resources of Medicago Genus and 32 germplasm resources of Trigonella Genus - Bingcheng Han; Xueming Dong; Mingyu Li; Zhaoming Wang; Congcong Shi; Qiang Zhou; Zhipeng Liu; Longfeng Yan (Scientific Reports)
Abstract Germplasm resources within the Medicago genus are highly regarded for their value as forage crops and their critical roles in nitrogen cycling, ecosystem restoration, and soil structure improvement. Therefore, understanding the diversity of seed morphology in this genus is essential for advancing its development and utilization. This study analyzed seed samples from 587 germplasm accessions representing 77 species within Medicago genus, as well as 32 accessions from 21 species within the closely related genus Trigonella. A statistical analysis was conducted on twelve traits, including seven quantitative traits-straight length (SL), straight width (SW), width-to-length ratio (WL), perimeter (PE), radicle length (RL), hilum length (HL), and 100-seed weight (SY)-and five qualitative traits, including seed coat condition, radicle characteristics, seed size, shape, and color. The results revealed that: (1) there was significant diversity (P < 0.05) in SL, SW, WL, PE, RL, HL, and SY across Medicago species; (2) principal component analysis of the 587 Medicago accessions identified SL, SW, PE, HL, RL, and SY as the primary contributors to morphological diversity; and (3) high-resolution images of seeds from various accessions were captured for future research. This study provides a solid foundation for the establishment of seed banks and the enhancement of germplasm resources through the systematic analysis of these morphological traits.